Quality of Life and Treatment Satisfaction in Participants with Maturity-Onset Diabetes of the Young: A Comparison to Other Major Forms of Diabetes - Dusatkova, Petra; Pavlikova, Marketa; Spirkova, Alena; Elblova, Lenka; Zdarska, Denisa Janickova; Rozenkova, Klara; Hron, Jakub; Sumnik, Zdenek; Cinek, Ondrej; Lebl, Jan; Pruhova, Stepanka (Experimental and clinical endocrinology & diabetes, 2022)
AIMS: We investigated the quality of life (QoL), treatment satisfaction and perception of genetic results in participants with Maturity-Onset Diabetes of the Young (MODY) and compared the results with those of subjects with type 1 (T1D) or type 2 (T2D) diabetes. METHODS: A total of 162 adults with GCK-MODY, 62 with HNF1A-MODY and 29 with HNF4A-MODY answered the questionnaire Audit of Diabetes Dependent Quality of Life, the Diabetes Treatment Satisfaction Questionnaire and non-validated instrument examining the respondent's perception of the genetic results. Data from GCK-MODY patients were compared with 84 participants with T2D and HNF-MODY subjects were compared with 81 participants having T1D. RESULTS: Higher age (p=0.004), higher haemoglobin A1c (p=0.026) and medication (p=0.019) were associated with lower general QoL in GCK-MODY patients. In HNF-MODY patients, lower general QoL was associated with a longer time since diagnosis (p=0.005), worse haemoglobin bA1c (p=0.006) and insulin treatment (p=0.019). Similar numbers of participants with GCK- and HNF-MODY considered the genetic diagnosis of MODY to be positive, negative and without significance. The patient with GCK-MODY did not differ from those with T2D in terms of their QoL, but they were less satisfied with their treatment (p<0.001). QoL was better in patients with HNF-MODY compared with patients with T1D (p=0.006), and they did not differ in terms of treatment satisfaction. CONCLUSIONS: QoL was affected in both GCK-MODY and HNF-MODY subjects. Apprehension of genetic diagnosis was not single-valued in MODY respondents.
Keywords: diabetes mellitus 2. typu; Young Adult; mladiství; Child; spokojenost pacientů; diabetes mellitus 1. typu; dítě; Adult; kvalita života; Diabetes Mellitus, Type 1; Diabetes Mellitus, Type 2; dospělí; lidé; Quality of Life; Patient Satisfaction; Humans; mladý dospělý; Adolescent